2022
DOI: 10.1371/journal.pone.0273847
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the very high caesarean section rate in urban areas of Vietnam

Abstract: Background Caesarean section and associated factors require detailed investigation globally. This study aims to determine the rate and associated factors of caesarean deliveries in urban areas of Vietnam. Methods A cross-sectional study using questionnaire answered by women who had infants aged under 30 months was conducted from March to May 2021. Data were collected in 18 commune health centres in two cities during the day of routine immunization. Multivariable logistic regression was performed to assess fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, this increase in cesarean deliveries was more evident in urban areas and at private hospitals. The reason for this rapid increase may be the preference of Vietnamese mothers in these settings due to their desire to avoid the harmful effects of vaginal delivery [44][45][46]. In the present study, 28.1% of Vietnamese mothers underwent cesarean section, and the prevalence of EIBF among mothers who underwent cesarean section was considerably lower than those who delivered vaginally (9.0% vs. 31.9%).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Moreover, this increase in cesarean deliveries was more evident in urban areas and at private hospitals. The reason for this rapid increase may be the preference of Vietnamese mothers in these settings due to their desire to avoid the harmful effects of vaginal delivery [44][45][46]. In the present study, 28.1% of Vietnamese mothers underwent cesarean section, and the prevalence of EIBF among mothers who underwent cesarean section was considerably lower than those who delivered vaginally (9.0% vs. 31.9%).…”
Section: Discussionmentioning
confidence: 48%
“…However, the rapid increase in the proportion of cesarean deliveries among Vietnamese mothers must have had a substantial effect. The proportion of cesarean deliveries in Vietnam drastically increased from 17% in 2011 to approximately 50% in the current time [44][45][46]. Moreover, this increase in cesarean deliveries was more evident in urban areas and at private hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,28 Unfortunately, the caesarean section rate in Vietnam are as high as 50% which are showed in both current study and previous studies. 29,30 .The results of our study showed that using bottle feeding of expressed breast milk to an infant was associated with decreased odds of continued breastfeeding at 12 months. In recent years, the prevalence of expressing breast milk has been increasing.…”
Section: Discussionmentioning
confidence: 56%
“…In Southeastern Brazil, the overall caesarean section rate was the highest rates among women whose deliveries were in a private health facility [ 27 ]. Similarly, the caesarean section rate in private hospitals (57.8%) was significantly higher than in public hospitals in Vietnam (49.1%) [ 28 ] and likewise in the Republic of Ireland (42.7% vs 25.3%) respectively [ 29 ]. One possible explanation for this increase in prevalence is that the hospital serves as a referral centre for the municipality and other adjourning districts, which may contribute to higher cases and a higher prevalence of caesarean section.…”
Section: Discussionmentioning
confidence: 99%